2010
DOI: 10.1111/j.1742-1241.2010.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NT-proBNP to predict outcomes in advanced heart failure

Abstract: Summary Aims:  To determine which factors predict outcomes in a group of patients with advanced heart failure, and in particular if NT‐proBNP provides additional clinical and prognostic information to other haemodynamic and biochemical data. Methods and Results:  Ninety‐one patients were studied who were being evaluated for heart transplantation, with 166 assessments. The patients had advanced heart failure as determined by median cardiac index of 2.0 l/min/m2, left ventricular end‐diastolic diameter of 7.0 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Elevated bilirubin levels have been shown to correlate with increased heart failure and death and corroborate the observations made with the previously mentioned biomarkers [30,25]. By contrast, other studies demonstrate that lower bilirubin levels correlate closely to coronary heart disease and metabolic syndrome components [31,32].…”
Section: Discussionsupporting
confidence: 80%
“…Elevated bilirubin levels have been shown to correlate with increased heart failure and death and corroborate the observations made with the previously mentioned biomarkers [30,25]. By contrast, other studies demonstrate that lower bilirubin levels correlate closely to coronary heart disease and metabolic syndrome components [31,32].…”
Section: Discussionsupporting
confidence: 80%
“…Bilirubin is known to correlate closely with right atrial pressure in HF patients. 12 Hemoglobin was decreased as a result of some perioperative blood loss. Of note, the significantly lower bilirubin level indicated that this lower hemoglobin was not related to hemolysis.…”
Section: Resultsmentioning
confidence: 99%
“…There were also significant increases in serum sodium and reductions in bilirubin indicating reduced neurohumoral activation 11 and reduced hepatic congestion, respectively. Bilirubin is known to correlate closely with right atrial pressure in HF patients 12 . Hemoglobin was decreased as a result of some perioperative blood loss.…”
Section: Resultsmentioning
confidence: 99%
“…In human subjects with DCM, the levels of β‐AR mRNA did not predict response to β‐blockers 31. In human heart failure, circulating NT‐proBNP correlates closely with cardiac index 32. Thus, the data on BNP mRNA from the myocardium of the mouse models seem to correlate well with clinical results, because the Sgcd null mice had the highest cardiac output and lowest levels of BNP mRNA at baseline, and overall emphasize the early stage of the cardiomyopathy in these mouse models.…”
Section: Discussionmentioning
confidence: 95%